Signaling involved in neurite outgrowth of postnatally born subventricular zone neurons in vitro - Khodosevich, Konstantin; Monyer, Hannah (BMC neuroscience, 2010)
Neurite outgrowth is a key process during neuronal migration and differentiation. Complex intracellular signaling is involved in the initiation of neurite protrusion and subsequent elongation. Although, in general many constituents of the machinery involved in this multi-stage process are common for neurons in distinct brain areas, there are notable differences between specific neuronal subtypes.